Diversity and abundance of bats (Chiroptera) found in bat boxes in east Lithuania - Baranauskas, Kazimieras (Acta Zoologica Lituanica, 2010)
Bat diversity and abundance was investigated in thirteen areas in east Lithuania in 2009. A total of 504 bat boxes of four models were checked in each area (30–60 bat boxes per area). The bat boxes were checked six times during the warm season of the year: in May, June, July, August, September and October. Six bat species, namely the Nathusius’ pipistrelle (Pipistrellus nathusii), soprano pipistrelle (P. pygmaeus), pond bat (Myotis dasycneme), brown long-eared bat (Plecotus auritus), noctule (Nyctalus noctula) and northern bat (Eptesicus nilssonii), were found in bat boxes. The Nathusius’ pipistrelle and soprano pipistrelle clearly dominated in the bat assemblage (accordingly, 79.3% and 18.4%). The breeding colonies of Nathusius’ pipistrelles and soprano pipistrelles were found in standard and four/five-chamber bat boxes. The breeding colonies of bats were constituted of approximately 30–150 individuals. Multichamber bat boxes in Lithuania were erected for the first time.